2008
DOI: 10.1016/j.jtcvs.2008.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Primary chest wall lymphoma with no history of tuberculous pyothorax: Diagnosis and treatment

Abstract: Treatment of primary chest wall lymphoma was not clear and various treatment strategies were considered. Remission of considerable duration in our patients leads us to suggest that surgery followed by adjuvant chemotherapy can provide a reasonable outcome in patients in whom the chest wall lymphoma is the only site of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In previous reports, when the tumors were identified, they were usually large with pleural effusion or atelectasis of the lung, independent of the tumor histology (13, 5). In the present case, the growth of the tumors was slow, which is a rare finding.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous reports, when the tumors were identified, they were usually large with pleural effusion or atelectasis of the lung, independent of the tumor histology (13, 5). In the present case, the growth of the tumors was slow, which is a rare finding.…”
Section: Discussionmentioning
confidence: 88%
“…Usually, primary pleural lymphoma is closely associated with chronic tuberculosis pyothorax, pneumothorax for treatment of lung tuberculosis, or some other chronic stimulation of B-cells such as rheumatoid arthritis, Sjögren's syndrome, or Epstein-Barr virus (3, 4). Considering these factors, primary malignant lymphoma arising in the chest wall without pre-existing pleural disease, as with the present case, are not common (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Review of literature corresponding to our 15‐year study period (2000‐2015) revealed 20 reports based either on cases series or isolated cases (Table ) in which 26 histologically confirmed chest wall lymphoma cases were described . Location of the swellings was the anterior chest wall/manubrium in 14 cases, left chest wall (four cases), right chest wall (three cases), lateral chest wall (NOS in two cases), back in one case and rib/chest wall swellings and NOS in two cases.…”
Section: Discussionmentioning
confidence: 99%